Monitoramento e modelagem da recarga freática em técnica de drenagem compensatória - Sírio, Daniel de Lima Nascimento (2013)
Stormwater flooding in urban centers today is the direct result of ground impermeabilization and the ineffective dimensioning of stormwater drainage systems. In order to control these events, innovative low impact stormwater drainage facilities are used in Brazil, which are efficient in controlling sharp peak flows in urban watersheds without, however, affecting the aesthetic appearance of the landscape in these environments. The purpose of this study is to model and estimate the volume of water infiltrated into the soil where a compensatory stormwater drainage system is inserted, which can contribute to groundwater recharge. Modeling was performed by means of a physical storage method and storage variation in soil using a tensiometer, and in digital form using the Hydrus 2D/3D software package. The monitored drainage system and the digitally designed system consist of a water retention basin, a ditch or filter, and an infiltration trench. Groundwater recharge was estimated based on soil analyses, geophysical investigations, flow measurements, and rainfall data, in addition to data collected during 454 days of continuous monitoring of the system by means of tensiometers installed on-site, rain gauges, and the construction of bimodal soil water retention curves using the filter paper method. The moisture content at different depths, the zero water flow plane, and the volumes moving in the soil matrix were calculated based on the identification of the soil water content and matric potential, the hydraulic conductivity in saturated conditions at the monitored depths, and the soil s characteristic curves. The results of the Soil Water Retention Curves (SWRC) and soil moisture content were negligible starting from a depth of 80cm. However, the groundwater recharge rate estimated by the tensiometer method and by the Hydrus digital model was about 45% of the total volume of rainfall.